On the Effects of Reactant Flow Rarefaction on Heterogeneous Catalysis: A Regularized Lattice Boltzmann Study (Communications in Computational Physics, 2020)
In this paper, a numerical investigation on heterogeneous catalysis is performedby means of a Regularized Lattice BGK approach. The effects of different valuesof the reactant flow Knudsen numbers are evaluated, in terms of conversion efficiency and penetration inside the structure of a nano-porous gold ingot. The results arein line with experimental evidence in the literature and open interesting perspectivesfor the optimal design of future nano-catalytic devices.
Keywords: Lattice Boltzmann; Nano-porous catalysts; heterogeneous catalysis.